The effectiveness of using educational cinema techniques to increase students' self-confidence: An experimental research - Utomo, Prio; Maratus, Sholihah (ProGCouns: Journal of Professionals in Guidance and Counseling, 2021)
This research is motivated by the problem of low self-confidence of students. The purpose of this study was to test the effectiveness of educational cinema techniques as a medium to increase students' low self-esteem. The research design used pre experimental research with one group pretest and posttest design. The research subjects were 16 students of class VIII SMPN 6 Malang, the subjects were selected using purposive sampling technique. Data collection used (1) self-confidence scale; (2) experimental guidelines and (3) observation guidelines. Data analysis used descriptive and statistical analysis (Wilcoxon signed rank test). The results of data analysis produce that H0 is rejected and H1 is accepted, this means that there is a significant increase in student self-confidence after being given educational cinema techniques. The findings of the study show that there are differences in the improvement of students 'self-confidence between before (pretest) and after (posttest) being given educational cinema techniques, thus the results of the study concluded that educational cinema techniques were effective in increasing students' self-confidence.